2022
DOI: 10.1039/d2sc01436j
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a transient base-stabilised arylalumylene for the facile deconstruction of aromatic molecules

Abstract: While a stable base-free arylalumylene bearing a sterically encumbered terphenyl substituent has been reported previously, we herein report that our attempts to form a base-stabilised arylalumylene bearing a relatively small...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 53 publications
(50 reference statements)
0
33
1
1
Order By: Relevance
“…Lewis-base-coordinated ferrocenyl-alane precursor 1 was synthesised by combining Fc*Li (Fc* = 2,5-bis(3,5-di- tert -butylphenyl)-1-ferrocenyl) 19 and NHC Me 4 AlH 3 (NHC Me 4 = 1,3,4,5-tetramethylimidazol-2-ylidene) 20 in equimolar amounts following our recently published strategy. 21 The treatment of 1 with an excess (5 equiv) of methyl iodide led to formation of Lewis-base-coordinated alkyldihaloalane precursor 2 ( Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lewis-base-coordinated ferrocenyl-alane precursor 1 was synthesised by combining Fc*Li (Fc* = 2,5-bis(3,5-di- tert -butylphenyl)-1-ferrocenyl) 19 and NHC Me 4 AlH 3 (NHC Me 4 = 1,3,4,5-tetramethylimidazol-2-ylidene) 20 in equimolar amounts following our recently published strategy. 21 The treatment of 1 with an excess (5 equiv) of methyl iodide led to formation of Lewis-base-coordinated alkyldihaloalane precursor 2 ( Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
“… 22 From our group, we also revealed that a transient base-stabilised alumylene can break the C–C bonds of benzene and toluene. 21 The synthesis of 4 is essentially a dialuminium analogue of the Birch reduction, 23 a novel outcome in aluminium chemistry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…benzene and toluene) furnishing dialuminium derivatives of pentalene 19a and 19b, respectively. [33] The dimerization of 18 to 16 is thermodynamically favored. The dimer 16 was not stable either and underwent an intramolecular [2 + 2] cycloaddition between the Al=Al double bond and the peripheral mesitylene ring affording 17 (Figure 5b).…”
Section: Synthon For Di-coordinate Aluminylenesmentioning
confidence: 99%
“…In addition, an intriguing class of nucleophilic anionic aluminyl compounds D [22–27] (Figure 1) has been rapidly developed and recently reviewed [5] . This concept focuses on the achievements of an emerging class of compounds C , namely free aluminylenes [28] or alanediyls (R−Al), as well as recent advances in their Lewis base complexes of type B [29–33] …”
Section: Introductionmentioning
confidence: 99%